Luminance, but not chromatic visual pathways, mediate amplification of conditioned danger signals in human visual cortex. Issue 9 (28th July 2013) - Keil, Andreas; Miskovic, Vladimir; Gray, Michael J.; Martinovic, Jasna
Abstract: Complex organisms rely on experience to optimize the function of perceptual and motor systems in situations relevant to survival. It is well established that visual cues reliably paired with danger are processed more efficiently than neutral cues, and that such facilitated sensory processing extends to low levels of the visual system. The neurophysiological mechanisms mediating biased sensory processing, however, are not well understood. Here we used grating stimuli specifically designed to engage luminance or chromatic pathways of the human visual system in a differential classical conditioning paradigm. Behavioral ratings and visual electroencephalographic steady‐state potentials were recorded in healthy human participants. Our findings indicate that the visuocortical response to high‐spatial‐frequency isoluminant (red–green) grating stimuli was not modulated by fear conditioning, but low‐contrast, low‐spatial‐frequency reversal of grayscale gratings resulted in pronounced conditioning effects. We conclude that sensory input conducted via the chromatic pathways into retinotopic visual cortex has limited access to the bi‐directional connectivity with brain networks mediating the acquisition and expression of fear, such as the amygdaloid complex. Conversely, luminance information is necessary to establish amplification of learned danger signals in hierarchically early regions of the visual system. Abstract : Experience shapes visual cortical processing in humans, but the mechanisms mediating experience‐related sensory changes are poorly understood. We used stimuli driving different aspects of the visual brain as conditioned threat cues in a classical differential fear‐conditioning paradigm. Electrophysiological recordings showed pronounced visuo‐cortical changes in retinotopic areas when threat was conveyed by luminance, but not chromatic stimuli.